Food & beverage cost control - Dopson, Lea R.; Hayes, David K. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2016)
'In order for foodservice managers to control costs effectively, they must have a firm grasp of accounting, marketing, and legal issues, as well as an understanding of food and beverage sanitation, production, and service methods. This fully updated sixth edition of Food and Beverage Cost Control provides students and managers with a wealth of comprehensive resources and the specific tools they need to keep costs low and profit margins high'--
Managing revenue and expense -- Creating sales forecasts -- Purchasing and receiving -- Managing inventory and production -- Monitoring food and beverage costs -- Managing food and beverage pricing -- Managing the cost of labor -- Controlling other expenses -- Analyzing results using the income statement -- Planning for profit -- Maintaining and improving the revenue control system.
Includes index.
Machine generated contents note: Preface Acknowledgments Chapter 1: Managing Revenue and Expense Professional Foodservice Manager Profit: The Reward for Service Getting Started Understanding the Income (Profit and Loss) Statement Understanding the Budget Chapter 2: Creating Sales Forecasts Importance of Forecasting Sales Sales Histories Maintaining Sales Histories Sales Variances Predicting Future Sales Apply What You Have Learned Key Terms and Concepts Test Your Skills Chapter 3: Purchasing and Receiving Forecasting Food Sales Forecasting Beverage Sales Importance of Standardized Recipes Purchasing Food Purchasing Beverages Purchase Orders Receiving Food and Beverage Products Chapter 4: Managing Inventory and Production Product Storage Storing Food Products Storing Beverage Products Inventory Control Product Issuing and Restocking Managing Food Production Managing Beverage Production Chapter 5: Monitoring Food and Beverage Product Costs Cost of Sales Computing Cost of Food Sold Computing Cost of Beverage Sold Computing Costs with Transfers Utilizing the Cost of Sales Formula Reducing the Cost of Sales Percentage Minimizing Product Loss in the Kitchen Minimizing Product Loss in the Bar Optimizing Overall Cost of Sales Percentage Chapter 6: Managing Food and Beverage Pricing Overview Chapter Outline Menu Formats Menu Specials Factors Affecting Menu Pricing Assigning Menu Prices Special Pricing Situations Chapter 7: Managing the Cost of Labor Labor Expense in the Hospitality Industry Evaluating Labor Productivity Maintaining a Productive Workforce Measuring Current Labor Productivity Managing Payroll Costs Reducing Labor-Related Costs Chapter 8: Controlling Other Expenses Other Expenses Controllable and Non-controllable Other Expenses Fixed, Variable, and Mixed Other Expenses Monitoring Other Expenses Managing Other Expenses Chapter 9: Analyzing Results Using the Income Statement Introduction to Financial Analysis Uniform System of Accounts Income Statement (USAR format) Analysis of Sales/Volume Analysis of Food Expense Analysis of Beverage Expense Analysis of Labor Expense Analysis of Other Expenses Analysis of Profits Chapter 10: Planning for Profit Financial Analysis and Profit Planning Menu Analysis Cost/Volume/Profit Analysis The Budget Developing the Budget Monitoring the Budget Chapter 11: Maintaining and Improving the Revenue Control System Revenue Security External Threats to Revenue Security Internal Threats to Revenue Security Developing the Revenue Security System The Complete Revenue Security System Glossary
Includes bibliographical references and index.
Keywords: Food service -- Cost control